Islamic Tolerance in Theory and Practice: Insights from Hadiths and Contemporary Relevance - Zaini, Muhammad (Prodi Ilmu Hadis Fakultas Ushuluddin dan Filsafat UIN Ar-Raniry Banda Aceh, 2024)
Tolerance is a fundamental principle in Islam that fosters social harmony within diverse societies. This study examines the concept of tolerance in Islam by focusing on the traditions (hadiths) of Prophet Muhammad (peace be upon him) and its implementation in social life. Employing a thematic (maudhū’i) approach, the research explores various dimensions of tolerance, including universal brotherhood, tolerance in mu’amalah (socio-economic interactions), respect for religious differences, and self-tolerance. The findings reveal that tolerance in Islam is not merely about accepting diversity but also reflects principles of compassion, justice, and moderation within the framework of Islamic law (sharia). Prophet Muhammad serves as a primary model in practicing tolerance, evident in his interactions and policies that upheld the rights of individuals and groups, including non-Muslims. This study underscores the relevance of Islamic tolerance in addressing the challenges of contemporary multicultural societies, offering a foundation for building harmonious relationships amidst diversity.